The effect of aloe vera and cabbage leaf (brassica oleracea) compresses on breast engorgement in postpartum mothers - Neng Suaidah; Agus Santi Br Ginting; Aan Maemunah; Ida Saidah; Sukmini Sukmini; Hafit Restu; Kurniasari Kurniasari; Meinasari Kurnia Dewi (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Breast engorgement is a common problem among postpartum mothers, characterized by breast tension, pain, and swelling due to obstructed milk flow. This condition can interfere with breastfeeding and may lead to complications if not properly managed. Purpose: This study aimed to determine the effect of aloe vera (Aloe vera) and cabbage leaf (Brassica oleracea) compresses on reducing the breast engorgement scale among postpartum mothers. Method: This study used a case study design with a Study Case Literature Review (SCLR) approach. The sample consisted of 6 postpartum mothers on days 3-7 experiencing breast engorgement, divided into two groups: the aloe vera compress group (3 respondents) and the cold cabbage leaf compress group (3 respondents). The intervention was carried out for 4 days, twice daily for 30 minutes. Breast engorgement was measured using the Six Point Engorgement Scale (SPES) over three visits. Results: The results showed that the aloe vera group experienced a decrease in the average breast engorgement scale from 5.00 to 1.33, with an average reduction of 3.66, while the cold cabbage leaf group showed a decrease from 5.00 to 1.00, with an average reduction of 4.00. Conclusion: Both interventions were effective in reducing breast engorgement; however, cold cabbage leaf compresses demonstrated higher effectiveness than aloe vera. Suggestion: It can be concluded that cold cabbage leaf and aloe vera compresses may be used as safe and simple non-pharmacological therapies for managing breast engorgement in postpartum mothers.